Relationship between hypertension with irrational health beliefs and health locus of control - Fatemeh Afsahi; Mohsen Kachooei (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Hypertension is one of the major health threats in the world today. The purpose of this study was to find the relationship between hypertension with irrational health belief and health locus of controls. MATERIALS AND METHODS: The current work is a descriptive (case-control) study. One hundred patients with hypertension and 100 healthy individuals were included in the study through available sampling method. The Irrational Health Belief Scale and Multidimensional Health Locus of Control questionnaire were used. Data were analyzed using independent t-test and logistic regression. RESULTS: The findings showed a significant relationship between the variables of irrational health beliefs and the external health locus of control in hypertension. For a unit increase in an irrational health belief score, the chance of having high blood pressure increases by 6%, and for a unit increase in the score of external health locus of control, there is a 17% higher chance of having hypertension. The independent t-test of irrational health belief also showed a statistically significant difference between the two groups (P < 0.01). There was also a statistically significant difference regarding the health locus of control in the two groups of hypertension and healthy individuals in the subscale of chance control (P < 0.01) and external locus of control (P < 0.01). CONCLUSION: The results of this study make it necessary to identify irrational health beliefs as well as the health locus of control in individuals. Modification of these structures can be useful in the prevention and management of this chronic disease.